Twin-twin transfusion syndrome: neurodevelopment of infants treated with laser surgery - Campos, Denise; Arias, Amabile V.; Campos-Zanelli, Thatiane M.; Souza, Daniela S.; Santos, Orlando G. dos, Neto; Peralta, Cleisson Fabio A.; Guerreiro, Marilisa M. (Arquivos de Neuro-Psiquiatria, 2016)
Objective To assess the neurodevelopmental functions of survivors of twin-twin transfusion syndrome (TTTS) treated by fetoscopic laser coagulation (FLC), during the first year of life, comparing them to a control group; and to verify the influence of specific variables on neurodevelopment.Method This was a prospective, longitudinal study. The sample comprised 33 monochorionic diamniotic twins who underwent FLC for treatment of TTTS and 22 full-term infants of single-fetus pregnancies. Bayley Scales of Infant and Toddler Development Screening Test were used for evaluation. Prenatal, perinatal and postnatal information were obtained.Results There was an increased frequency of infants in the TTTS group with inadequate performance compared to the control group. The identified variables (fetal donor, low economic income and cardiorespiratory disease) negatively impacted expressive communication and fine motor skills.Conclusion Although through follow-up is recommended in all TTTS survivors, particular attention is required for the high-risk group as defined in this study.
Keywords: diseases in twins; fetofetal transfusion; child development; risk factors